KOMUNIKASI CUSTOMER SERVICE REPRESENTATIVE (CSR) DALAM PEMBERIAN INFORMASI KEPADA PELANGGAN DI PLASA TELKOM SUDIRMAN PEKANBARU - Muharman Febrianda; Rusmadi Awza (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Effective communication is delivering idea, message, and feeling in a best way and reaching its purpose. Plasa Telkom is a place established by PT TELKOM as a media to serve customer’s needs or soon to be customer’s personally and face to face. The purpose of this research is to know how the communication of Customer Service Representative in appreciating their customers in plasa Telkom sudirman pekanbaru and also to know the obstacles and supportive factors of Customer Service Representative in delivering information in plasa Telkom sudirmana pekanbaru.This research used descriptive qualitative method. Data gathering technique used was in accordance to the fact shown in field by observing, interviewing, and documenting. It used 6 informants based on the purposive sampling and accidental sampling methods. Data analysis technique used was organizational information theory and analysis data interactive model. While for the data validity, researcher used long term participation technique and triangulation.The results shown, there are four main points that needed to be looked at in delivering information, which are language, media, communication duration, and communication method. Those points are really important in the communication of Customer Service Representation (CSR) in delivering information to customers in plasa Telkom sudirman pekanbaru. The obstacle factors are lack of coordination between CSR and field staffs, customer education background, and customer emotion. While thesupportive factor are support facilities, backroom’s support, and understandable CSR supportive application.Keyword: Communication, Customer Service Representative, Information